EPHB4 tyrosine‐kinase receptor expression and biological significance in soft tissue sarcoma. Issue 8 (18th October 2014) - Becerikli, M.; Merwart, B.; Lam, M.C.; Suppelna, P.; Rittig, A.; Mirmohammedsadegh, A.; Stricker, I.; Theiss, C.; Singer, B.B.; Jacobsen, F.; Steinstraesser, L.
<x xml:space="preserve">Abstract</x> Soft tissue sarcomas (STS) are heterogeneous malignant tumors of mesenchymal origin. Due to low incidence and high number of different histological subtypes, their pathogenesis and thus potential targets for their therapy remain barely investigated. Several studies revealed significant higher EPHB4 expression in malignancies such as prostate and colorectal cancer showing survival advantages for these tumor cells. Therefore we studied the expression of EPHB4 in a total of 46 clinical human specimens of different STS and human fibroblasts. EPHB4 mRNA and protein expression were significantly increased in synovial sarcoma. After targeting EPHB4 in fibrosarcoma, synovial sarcoma, liposarcoma and MFH sarcoma cell lines by siRNA or by inhibition of autophosphorylation using the specific EPHB4 kinase inhibitor NVP‐BHG712 a decreased proliferation rate/vitality of synovial‐ and fibrosarcoma cells was observed. Silencing of EPHB4 significantly reduced the transmigration of synovial sarcoma cells towards fibroblasts and endothelial cells. In addition, we assessed the anti‐metastatic effect of EPHB4 inhibition in vivo by intraperitoneal administration of the EPHB4 inhibitor in an appropriate sarcoma lung metastasis xenograft model. As result 43% of NVP‐BHG712 treated mice (n = 3/7) developed pulmonary metastases whereas all control mice (n = 5) revealed lung metastases. The residual 57% of mice (n = 4/7) showed only small local tumor cell spots. Size measurements of the Vimentin positive area explained significant decrease in lung metastasis formation (p < 0.05) after EPHB4 kinase inhibition. In summary, these data provide first evidence of the importance of EPHB4 in the tumorigenesis of synovial sarcoma and present EPHB4 as a potential target in the therapy of this malignancy.